The Experience of Loneliness with Regard to Gender and Type of Study among University Students (European Journal of Behavioral Sciences, 2023)
Loneliness is usually defined as an unpleasant and emotionally disturbing subjective experience that occurs as response to the discrepancy between desired and achieved levels of social contact. The experience of loneliness is unpleasant and painful experience, followed by feelings of rejection from the people that we care, with simultaneous desire that they accept us and to be part of their lives. The main aim of this study was to examine the differences in loneliness with regard to gender, that is, to determine whether young men and women experience different levels of loneliness and also to determine whether there is a difference in the level of loneliness between students of social sciences and students of technical sciences. The study was conducted on a sample of 200 students (82 males and 118 females) of various departments of the final year of Social Sciences and Technical Sciences at the University of Tuzla, Bosnia and Herzegowina. The study applied the following instruments: The short version of UCLA loneliness scale and examination of gender and studies based on rounding on the questionnaire. The results showed a statistically significant difference in the level of loneliness for men (Md=15.00, n=82) and women (Md=11.05, n=118), U = 3954, z = -2.203, p